6(2x-1)=18

Simple and best practice solution for 6(2x-1)=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-1)=18 equation:


Simplifying
6(2x + -1) = 18

Reorder the terms:
6(-1 + 2x) = 18
(-1 * 6 + 2x * 6) = 18
(-6 + 12x) = 18

Solving
-6 + 12x = 18

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 12x = 18 + 6

Combine like terms: -6 + 6 = 0
0 + 12x = 18 + 6
12x = 18 + 6

Combine like terms: 18 + 6 = 24
12x = 24

Divide each side by '12'.
x = 2

Simplifying
x = 2

See similar equations:

| -0.25y=-5 | | 12=2(k+1) | | 4+14x=4-6x | | 4(3m+5)-14=42 | | 28=3s-4b | | 4d-6d=-2 | | 7n/9-62=5n/9-48 | | 9y-4x=-16 | | 0.6(15+0.5)-0.9(25-1)= | | 69=60+9-2+3-1 | | 69=60+9-2+3 | | 3y+12=4y-2y+1 | | 12c-6=44 | | 69=60+8 | | .625m-.375=.5m+.875 | | x/3-2/9=4/9 | | 15n=290 | | -6m=-6m^2+5(-6m) | | x+3+2x-5=19 | | 17+3m=5m+9 | | y=3(4)*-1 | | x=180-(7x-12) | | -7(-1+3x)=5(3-5x) | | 35(8x-20)-18=-718 | | 6(x-4)=-5(2x+2) | | m^2-8m-33=0 | | x+3+2x+5=19 | | l^2-6l-91=0 | | -6-x=15+2x | | 3p(-4)=13 | | 3(x-2)+4=2x+6 | | 13.95x=558 |

Equations solver categories